Encyclopedia of Analytical Chemistry 2018
DOI: 10.1002/9780470027318.a9419
|View full text |Cite
|
Sign up to set email alerts
|

Microrheology of Biological Specimens

Abstract: A great number of important biological phenomena that occur in living organisms demand energy transduction processes that critically depend on the viscoelastic properties of their constituent building blocks, such as cytoplasm, microtubules, and motor proteins. Accordingly, several techniques have been developed to characterize biological systems with complex mechanical properties at micron‐ and nano‐length scales; these are now part of an established field of study known as Microrheology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…When a micron-sized spherical particle is suspended into a viscoelastic fluid at thermal equilibrium, it experiences random forces leading to its Brownian motion, which is driven by the thermal fluctuations of the fluid's molecules. It has been shown that the statistical mechanic analysis of the bead trajectory r(t) ∀ t can be directly related to the linear viscoelastic properties of the surrounding environment by solving a generalized Langevin Equation: [42,45] m a(t…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a micron-sized spherical particle is suspended into a viscoelastic fluid at thermal equilibrium, it experiences random forces leading to its Brownian motion, which is driven by the thermal fluctuations of the fluid's molecules. It has been shown that the statistical mechanic analysis of the bead trajectory r(t) ∀ t can be directly related to the linear viscoelastic properties of the surrounding environment by solving a generalized Langevin Equation: [42,45] m a(t…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been shown that there exists a link between microrheology and bulk rheology measurements. [42,45] This is obtained by retrieving the constitutive equation between the material's shear relaxation modulus G(t) and its shear compliance J(t):…”
Section: Methodsmentioning
confidence: 99%
“…In particular, one can explore passive experimental approaches (e.g., particle tracking videomicroscopy or dynamic light scattering; see Ref. [1] for a review) to extract the mean-squared displacement (MSD) ∆r 2 (τ) a of probe particles with radius a and relate it to the compliance J(τ) of the so-lution through a generalized Stokes-Einstein relationship [20,23], that is,…”
Section: Viscoelasticity Of Unentangled Solutionsmentioning
confidence: 99%
“…Despite of its importance to the well-functioning of almost all biological specimens [1], the viscoelastic response of complex solutions of unentangled semiflexible filaments [2], e.g., collagen, actin, rodlike viruses, amyloid fibrils, microtubules, and DNA, is not yet entirely predictable neither from theory or simulations [3]. Contrary to solutions of cross-linked filaments, where a shear protocol can be used to extract the mechanical properties of the networks [4,5,6,7], the study of the viscoelastic response of solutions of diluted unentangled filaments relies mainly on monitoring the stochastic dynamics of segments in the filament, which means that those methods are based mainly on fluctuations due to Brownian dynamics [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although held by the trap, the bead still undergoes Brownian motion within a finite volume defined by the trap, and its trajectory can be traced and analysed to deduce the viscoelastic properties of the suspending media. This has proved to be a highly effective technique, especially for the analysis of biological samples [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%